Pendampingan Kepala Sekolah Dalam Supak Daring Dengan Strategi Supervisi Kolaboratif Melalui WA Zoom Selama Masa Adaptasi Kebiasaan Baru - Agon Agon (FKIP, Universitas Palangka Raya, 2022)
The implementation of distance learning, to support the learning from home (BDR) policy in the emergency period of the spread of Covid-19, has led to various findings that are worthy of study and discussion, especially regarding supervision instruments and the online academic supervision process. This research aims to assist school principals in online supervision with a collaborative strategy through WA Zoom. During the adaptation period of this new habit, schools really need to carry out academic supervision in the implementation of PJJ, both online and offline. Because without academic supervision, the principal will not know about the progress and extent of PPJ implementation. The expected result of the supervisor's assistance to the principal of the target school is that the principal is able to carry out academic supervision of the implementation of PJJ.